SURVEI KONDISI FISIK PEMAIN SEPAK BOLA LIGA 3 INDONESIA PADA TIM PS. SIAK - Zendrato, Sajanolo; Ramadi, Ramadi; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: These changes have a very good impact on future development,especially the physical, technical, tactical, and mental condition of the players. Physicalcondition is a problem in the competition for achievement because no matter how greata person is in terms of technique and tactics, if it is not supported by excellent physicalcondition, it will be a problem for an athlete to achieve achievements in his field. Thisresearch is a quantitative research with a descriptive approach method which is aresearch plan that has the purpose of explaining or describing systematically, factuallyand objectively accurately. The sample in this study is 21 people from the PS. Siak team,the data that will be collected in this study is a physical condition test consisting ofstrength tests (sit up and push ups), speed (100 meter sprint), agility (illinois run),explosive power (vertical jump), endurance (15-minute run). The data analysistechnique used is a quantitative descriptive analysis technique with percentages. Basedon the results of the analysis, the physical condition of Indonesian Liga 3 footballplayers in the PS. Siak team is in the good category with a percentage of 57.14% with12 athletes. In this case, the physical condition of the athlete needs to be a specialconcern for the coach as an evaluation material both from the evaluation of the trainingprogram, the implementation of the training program and how to condition the athletewhen carrying out the planned training program.Key Words: Physical Condition, Football, League 3